Monetary policy: theory, international history and applications in Argentina (Cultura Económica, 2022)
Historically, money has always occupied a central place in economic theory. The perception of its role and its influence have changed over time and, although there is quite general consensus, it is still controversial today. Monetary policy, that is, the management of its supply based on several objectives, has also evolved over time along theoretical advances and historical situations. In this article, I intend to review how the criteria that govern its actions have changed and the challenges that currently exist at a global level, as well as analyze the evolution of monetary policy in Argentina within that context.
Keywords: BUSINESS FLUCTUATIONS; CYCLES; MONETARY SYSTEMS; STANDARDS; REGIMES; GOVERNMENT AND THE MONETARY SYSTEM; PAYMENT SYSTEMS; MONETARY POLICY; CENTRAL BANKS AND THEIR POLICIES